Personhood, self-consciousness, and the first-person perspective - Herrmann, Markus (Brill mentis, 2023)
Self-consciousness, first-person reference, and personal identity are linked fields of research. The book contains contributions from international researchers about topics like pre-reflective and reflexive consciousness, embodiment, temporality, self-location, and the practical implications of personal identity. Among the contributors are Amit Anurag, Irene Breuer, Tony Cheng, Heidi Haanila, Markus Herrmann, Muriel Leuenberger, Maik Niemeck and Jörg Noller.